2013
DOI: 10.1364/ol.38.000332
|View full text |Cite
|
Sign up to set email alerts
|

Combination of spectral and fluorescence imaging microscopy for wide-field in vivo analysis of microvessel blood supply and oxygenation

Abstract: Hyperspectral imaging of hemoglobin (Hb) saturation and first-pass fluorescence imaging of blood transit time were combined to analyze the oxygenation of and blood flow through microvessel networks. The combination imaging technique was demonstrated in a mouse dorsal window chamber model of a growing Caki-2 human renal cell carcinoma over time. Data from Hb saturation and blood supply time maps show the formation of arteriovenous malformations and shunting of blood directly from arteries to the tumor core and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…88 Although most of these studies were mainly concentrated on the system design, and only preliminary results have been obtained, they have demonstrated the possibility of inspecting inner regions of the human body with additional diagnostic information by spectral imaging technology. There are also some other in vivo applications of spectral imaging systems, such as hemoglobin saturation evaluation in tumor microvasculature and tumor hypoxia development, 91 characterization of activity-dependent changes in oxyhemoglobim, deoxyhemoglobim, and light scattering in brain, 197 analysis of the oxygenation and blood flow through microvessel networks, 198 normal and malignant muscle tissues detection, 84 tooth decay detection, 82,113,185 and flow cytometry. 86 Guidance of surgical intervention, treatment, and real-time assessment of tissue response to therapy is another promising application of in vivo spectral imaging.…”
Section: In Vivo Spectral Imagingmentioning
confidence: 99%
“…88 Although most of these studies were mainly concentrated on the system design, and only preliminary results have been obtained, they have demonstrated the possibility of inspecting inner regions of the human body with additional diagnostic information by spectral imaging technology. There are also some other in vivo applications of spectral imaging systems, such as hemoglobin saturation evaluation in tumor microvasculature and tumor hypoxia development, 91 characterization of activity-dependent changes in oxyhemoglobim, deoxyhemoglobim, and light scattering in brain, 197 analysis of the oxygenation and blood flow through microvessel networks, 198 normal and malignant muscle tissues detection, 84 tooth decay detection, 82,113,185 and flow cytometry. 86 Guidance of surgical intervention, treatment, and real-time assessment of tissue response to therapy is another promising application of in vivo spectral imaging.…”
Section: In Vivo Spectral Imagingmentioning
confidence: 99%
“…(E) Hyperspectral imaging of sO 2 in a Caki-2 tumor–bearing dorsal skinfold window chamber 4 days following tumor implantation. Images adapted with permission from Lee JA et al 117 (F) Hemoglobin saturation ( top ) and flavin adenine dinucleotide (FAD)/reduced nicotinamide adenine dinucleotide (NADH) ratiometric redox ( bottom ) imaging in a non–tumor-bearing window chamber mouse during oxygen and nitrogen inhalation. Hemoglobin saturation was measured by absorption between the wavelength range of 500 to 620 nm, whereas redox was calculated based on NADH and FAD autofluorescence.…”
Section: Tumor Hypoxiamentioning
confidence: 99%
“…115 Hyperspectral imaging has been used in combination with video recording of blood flow to study the course of wound-induced vascular abnormalities in the dorsal WC model. 116 Similarly, hyperspectral imaging and fluorescence imaging of blood transit time have been used in combination to analyze vascular oxygenation and blood flow 117 (see Figure 5E). Both PAM and hyperspectral imaging can be used in a similar manner to phosphorescence imaging for studying alterations in vascular oxygenation following radiation, thereby obtaining simultaneous information on blood flow when integrated with other imaging systems.…”
Section: Tumor Hypoxiamentioning
confidence: 99%
“…Hyperspectral intravital imaging has been pioneered for tumor biology by Sorg, Dewhirst and colleagues, initially to investigate the spatial relationship between microvascular sO 2 and tumor response to hypoxia, using tumor cells engineered to express green fluorescent protein (GFP) under the control of a HRE (Sorg et al, 2005). Other basic studies have investigated the relationship between fluctuations in tumor micro-vascular oxygenation and the location of arterio-venous shunts (Sorg et al, 2008), macrophage infiltration (Choe et al, 2010) and blood flow using the BST method described above (Lee et al, 2013). Studies of therapy have demonstrated reoxygenation of tumors following radiation treatment, which correlated with an increase in glycolysis (Zhong et al, 2013) and hypoxia-induction followed by reoxygenation induced by the vascular disrupting agent, Oxi4503 (Wankhede et al, 2010).…”
Section: Hemoglobin Oxygen Saturationmentioning
confidence: 99%